Answer:
x = 8; y = -6
Step-by-step explanation:
We have a system of equations.
[tex] \dfrac{3(x - 2)}{2} - \dfrac{y - 2}{4} = 11 [/tex]
[tex] \dfrac{2(x + 2)}{5} - \dfrac{y}{3} = 6 [/tex]
First, let's multiply both sides of each equation by the LCM of both denominators of that equation to eliminate all denominators.
First equation:
[tex] 8 \times \dfrac{3(x - 2)}{2} - 8 \times \dfrac{y - 2}{4} = 8 \times 11 [/tex]
[tex] 12(x - 2) - 2(y - 2) = 88 [/tex]
[tex] 12x - 24 - 2y + 4 = 88 [/tex]
[tex] 12x - 2y = 108 [/tex]
[tex] 6x - y = 54 [/tex]
The equation above is the simplified first equation.
Second equation:
[tex] \dfrac{2(x + 2)}{5} - \dfrac{y}{3} = 6 [/tex]
[tex] 15 \times \dfrac{2(x + 2)}{5} - 15 \times \dfrac{y}{3} = 15 \times 6 [/tex]
[tex] 6(x + 2) - 5y = 90 [/tex]
[tex] 6x + 12 - 5y = 90 [/tex]
[tex] 6x - 5y = 78 [/tex]
The equation above is the simplified second equation.
The simplified system of equations is:
[tex] 6x - y = 54 [/tex]
[tex] 6x - 5y = 78 [/tex]
The x term of both equations is 6x. If we multiply both sides of the second equation by -1 to get a first term of -6x, then when it is added to 6x, the x terms are eliminated.
Now we rewrite the first simplified equation as it is. Below it, we write the second equation multiplied by -1 on both sides. Then we add the equations.
[tex] 6x - y = 54 [/tex]
[tex] -6x + 5y = -78 [/tex]
Add the equations to get:
[tex] 4y = -24 [/tex]
[tex] y = -6 [/tex]
Now we substitute -6 for y in the first simplified equation and solve for x.
[tex] 6x - y = 54 [/tex]
[tex] 6x - (-6) = 54 [/tex]
[tex] 6x + 6 = 54 [/tex]
[tex] 6x = 48 [/tex]
[tex] x = 8 [/tex]
Solution: x = 8; y = -6